RELEVANSI TEORI MALTHUS DALAM DISKURSUS KEPENDUDUKAN KONTEMPORER - Subair Subair (IAIN Ambon, 2018)
The higher the number of the population at any given time, more and more babies are being born, and resulted in a population at higher next generation. The world's population growth will be faster to follow an exponential growth, while the carrying capacity of the environment such as the availability of land and water increases follow an arithmetic progression. At one time, the total population will exceed the availability of the resources needed (Thomas Malthus)